Features and origin of Billurik dere (Elazig) mineralizations - Sasmaz, A.; Sagiroglu, A. (My University, 1990)
Mineralization of Billurik dere is located in and on the contact zone of granitic and dioritic magmatics of the Yuksekova complex. The mineralization occurs in E-W striking tension fractures and is of vein type. The mineral assemblages of these veins are pyrite, chalcopyrite, sphalerite, galena, magnetite and specularite. The mineralizations which occur on the contact zones are contact type in nature and they bear additional minerals such as Cu-sulphosalts, Bi-sulphosalts and Ag-fahlore. The mineralizations are associated with sericitization, kaolinization, silicification; tourmalinization and epidote formation. -from Authors
Keywords: Billurik Dere; Turkey; contact zone; igneous intrusion; mineralization; vein type deposit